Public, Private and Foreign Investment Nexus in the Republic of North Macedonia: Crowding-In or Out Effect? - Vesna Garvanlieva Andonova (Economy, Business and Development: An International Journal (EB&D), 2022)
The last two decades' economic growth of North Macedonia can be qualified as sluggish and volatile. During this period, the government has been proclaiming a narrative of fiscal and economic policies focused on public investment driven development and growth, yet the capital budget bias, has been significant with regularly overestimated plans vs. the outturn. The public investment-to-GDP ratio, has been an average 5.47%, ranging from minimum 4.0% (Y2007) to maximum 6.7% (Y2010). Simultaneously, the private investment-to-GDP ratio has been an average 17.1%, with minimum of 15% (in Y2005) and a maximum value of 20.6% (in Y2008). The FDI inflows, have been ranging from minimal below 1% in Y2014 to a maximum 12.7% in Y2001, with average of 4.6% per annum. The trends of the variables straightforwardly do not suggest a nexus between the public and private investments i.e. crowding-in or crowding out effect. This paper investigates whether public investment and foreign direct investments crowd-out or crowd-in the private investment in North Macedonia. To test this hypothesis, we use the available annual data on private, public & foreign direct investments and GDP for the period of 2000-2017, with a model of autoregressive distributed lag bound testing. The results indicate crowding-out effect of public over private investments with significance of the foreign direct investments variable and crowding-in effect of foreign direct investments over private domestic investments. The crowding-out effect is immediate and short run.
Keywords: E22; H54; H11; 330; ARDL bound testing; crowding-out effect; private investment; public investment